Pengaruh Tingkat Kepadatan Penduduk Yang Semakin Kompleks dan Terus Meningkat di Kota Surabaya - Kinanti R Hayati; Anatasya Rachma C; M. Ferry Firmansyah; Rania Nurlita Sari (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Population density is an important problem and often occurs in urban environments. This can lead to new problems, such as an emphasis on the availability of water, infrastructure, energy, electricity, health services and sanitation. Based on the World Population Data Sheet (2014), Indonesia is the 4th country in the world with an estimated population of 251.5 million. Indonesia among ASEAN countries is a country with a fertility rate or Total Fertility Rate of 2.6, where Indonesia is above the average TFR of 2.4. The method used, namely qualitative analysis techniques with an ethnographic communication approach is used to achieve the research objectives. Data were obtained through participatory observation and interview methods with recording and note-taking techniques. Based on the results of the respondents, it is known that the level of population density in the city of Surabaya is uneven, the population density assessment is known that population growth in the city of Surabaya is considered quite bad, as seen from the results of the respondents with an acquisition of 56.7%. The economy is a crucial aspect that causes population density. Therefore, it is necessary to do both the government and its citizens so that the government and society need to work together to strive for balanced and sustainable population density control.